2018
DOI: 10.1074/jbc.m117.819300
|View full text |Cite
|
Sign up to set email alerts
|

The plant sesquiterpene lactone parthenolide inhibits Wnt/β-catenin signaling by blocking synthesis of the transcriptional regulators TCF4/LEF1

Abstract: The Wnt/β-catenin pathway is essential for embryonic development and homeostasis, but excessive activation of this pathway is frequently observed in various human diseases, including cancer. Current therapeutic drugs targeting the Wnt pathway often lack sufficient efficacy, and new compounds targeting this pathway are therefore greatly needed. Here we report that the plant-derived natural product parthenolide (PTL), a sesquiterpene lactone, inhibits Wnt signaling. We found that PTL dose-dependently inhibits Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…WNT2B interacts with frizzled receptor and activates the Wnt signaling pathway, which leads to the increased expression of β-catenin in the cytoplasm (23). Subsequently, the β-catenin protein translocates from the cytoplasm into the nucleus and promotes the transcriptional effect of TcF4 (28,29). Previous studies have reported that WNT2B acts as an oncogene in a number of tumors and is positively associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…WNT2B interacts with frizzled receptor and activates the Wnt signaling pathway, which leads to the increased expression of β-catenin in the cytoplasm (23). Subsequently, the β-catenin protein translocates from the cytoplasm into the nucleus and promotes the transcriptional effect of TcF4 (28,29). Previous studies have reported that WNT2B acts as an oncogene in a number of tumors and is positively associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid progress in transcriptome sequencing, different lncRNAs are being identified to be related to different diseases, including RA. 23,24 Previous study indicated the potential role of MEG3 in RA. 25 Also, it is important to understand the effect of MEG3 in RA as well as the underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid progress in transcriptome sequencing, different lncRNAs are being identified to be related to different diseases, including RA . Previous study indicated the potential role of MEG3 in RA .…”
Section: Discussionmentioning
confidence: 99%
“…RPL10 is a component of the 60S ribosome. The use of parthenolide probe showed that deprivation of RPL10 decreased the levels of TCF4/LEF1 but had no effects on β-catenin levels, indicating a selectivity of the 60S ribosome in regulating protein synthesis (Zhu et al, 2018).…”
Section: Plant Natural Product Modulators Of Wnt Signalingmentioning
confidence: 99%